Study Tour of the Development of Tourism Business on the Mangrove Beach of Nipah Village, Sei Nagalawan, Serdang Bedagai - Rotua SP Simanullang; Ellys Siregar; Gartima Sitanggang; Aurora Elise Putriku (Outline Journal of Community Development, 2025)
This activity aims to establish cooperation between the Office Administration Education Study Program in the Tourism Business course with the Community Group managing the Nipah Village Mangrove Beach in Sei Nagalawan Serdang Bedagai. Students learn to build a business spirit from the speakers who manage the mangrove beach from zero to the current semester conditions and partners will benefit from students helping to promote this mangrove beach through their social media and providing ideas for the development of Sei Nagalawan mangrove tourism through the contribution of creative ideas from the current generation through input on the engineering of ideas provided. help partners in promoting the mangrove beach. This activity took place on Thursday, October 9, 2024 for 1 full day. The targets and forms of activities are: 1) Dialogue and discussion with the speaker Mr. Tris as the head of the Sei Nagalawan Community group; 2) Mini Research by dividing teams into groups accompanied by one campus team leader and 1 assistant from the tourism manager; 3) Formulation of results and development of ideas; 4) Joint presentation of results and provision of recommendations The main targets of this activity are: 1) the production of recommendations for developing ideas from each group for the development of the Sei Nagalawan Mangrove Beach and 2) Promotional media produced by students on social media in the form of travel notes.